2013
DOI: 10.5402/2013/427230
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Kidney Disease and Its Related Risk Factors in Elderly of Southern Iran: A Population-Based Study

Abstract: Aim. The prevalence of chronic kidney disease (CKD) as a serious public health problem is growing in the elderly. This study aimed to assess CKD prevalence and its related risk factors in elderly population of Fars province. Methods. In this cross sectional study a total of 1190 elderly people are enrolled, and demographic and medical data were obtained. Data were analyzed by SPSS, and P of less than 0.05 was considered as statistically significant. Results. Prevalence of CKD stages III–V was 27.5% in the 60–6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…In agreement with previous studies of western countries which specified an increasing trend toward incidence of urinary bladder and kidney cancers (22), in this study incidence of urinary system cancers 23.2% was increased between 2011 and 2015. Previous publications confirmed that, there is a change to older-in-age scattering in Iran as a developing country (23). In agreement with previous publications that mentioned the mean age of diagnosis of 65 years (24), in this study also the mean age of patients was also 63.6 years old.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with previous studies of western countries which specified an increasing trend toward incidence of urinary bladder and kidney cancers (22), in this study incidence of urinary system cancers 23.2% was increased between 2011 and 2015. Previous publications confirmed that, there is a change to older-in-age scattering in Iran as a developing country (23). In agreement with previous publications that mentioned the mean age of diagnosis of 65 years (24), in this study also the mean age of patients was also 63.6 years old.…”
Section: Discussionsupporting
confidence: 92%
“…Nine studies were obtained from six provinces. Of the nine studies, two studies each were from Tehran , Golestan , and Fars , respectively. In other provinces including Isfahan , Razavi Khorasan , and Kerman , one study was conducted in each.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies in Iran demonstrated that female gender was the strongest risk factor for CKD. 13,29 However, in this study, as table 1 shows, there were associations between GFR and gender, serum creatinine and gender( p <0.001).Around 17.6% of males and 7.1% of females had moderately reduced GFR, and 0.7% of males and 0.5% of femaleshad severely reduced GFR. Therefore, the indices for renal function in females are generally better than in males.…”
Section: Discussionmentioning
confidence: 47%